A preliminary study of the effects of learning styles on learner autonomy among Chinese non-English majors: Learning engagement as a mediator - Xiaojun, Cao; Yusoff , Muhammad Saiful Anuar; Wan Mohamed, Wan Nazihah (Journal of Islamic, Social, Economics and Development, 2026)
Learner autonomy is a core outcome of higher education and a key objective in EFL ‎pedagogy, yet its antecedents remain underexplored in Asian tertiary contexts. This‎ preliminary study investigated how learning styles and learning engagement affected learner ‎autonomy among non-English major undergraduates in Xi’an, China. Using a ‎quantitative cross-sectional design, data were collected from 100 students across six ‎universities via a validated self-report questionnaire. Partial Least Squares Structural ‎Equation Modelling (PLS-SEM) was employed for data analysis. Results showed that ‎the four learning style modes (Concrete Experience, Reflective Observation, Abstract ‎Conceptualisation, and Active Experimentation) did not directly predict learner ‎autonomy. Autonomy was found to be significantly predicted by learning engagement ‎‎( β = 0.562, t = 4.021). The results of the mediation analysis indicated that the effects of abstract conceptualization and active experimentation on autonomy were significantly mediated by engagement, with coefficients of (β = 0.164, t = 2.246) and (β = 0.250, t = 2.750) respectively. These results point to engagement as a crucial psychological ‎mechanism that connects learning styles to independent learning and offer ‎recommendations for future large-scale studies.‎